Child Amputee Prosthetics Project—Prosthesis Satisfaction Inventory (CAPP-PSI): Validation of Italian Version in Children with Upper Limb Amputation - Luigino Santecchia; Gessica Della Bella; Francesca Caspi; Paola Luttazi; Lorenzo Pochiero; Fabrizio Taffoni; Giordana Mariani; Marco Gaudenzi; Donatella Valente; Marco Tofani (Children)
Background: The Child Amputee Prosthetics Project—Prosthesis Satisfaction Inventory (CAPP-PSI) is a comprehensive instrument designed to measure satisfaction across functionality, aesthetic, and service domains. This study aimed to translate, culturally adapt, and evaluate the psychometric properties of the CAPP-PSI in an Italian pediatric population. Methods: Following international guidelines, the CAPP-PSI was translated and culturally adapted. Internal consistency was evaluated using Cronbach’s alpha, while test–retest reliability was assessed with intraclass correlation coefficients (ICCs). Construct validity was measured by analyzing correlations among subscales. Results: A total of 113 children with congenital or acquired upper limb amputation, accompanied by their parents, were recruited from the Bambino Gesù Children’s Hospital in Rome. The Italian CAPP-PSI demonstrated excellent internal consistency (Cronbach’s alpha = 0.913) and strong test–retest reliability (ICC = 0.966). Subscale correlations showed strong relationships between child and parent satisfaction (r = 0.724, p < 0.01) and parent satisfaction with service (r = 0.612, p < 0.01), while moderate correlations were observed between child satisfaction and service (r = 0.434, p < 0.01). Conclusions: The Italian version of the CAPP-PSI is a reliable and valid tool for assessing prosthetic satisfaction in pediatric populations. It provides valuable insights for clinicians and researchers, supporting patient-centered care and targeted improvements in prosthetic design and services. Future studies should explore longitudinal outcomes and the role of psychosocial factors in prosthetic acceptance.